The Influence of Customer Lifestyles on the Use of Mobile Banking Applications in Lampung - Sunarmi; Milan Juliyana (Institute of Computer Science (IOCS), 2023)
Advances in technology provide convenience for each company in developing its business, especially in establishing communication with its customers. The banking business has implemented an information system by maximizing the use of the Mobile Banking application. This technology focuses on providing financial banking services using Android devices and is the main transaction for today's diverse daily needs. This study aims to clarify the importance of mobile banking applications in the banking sector in Lampung. The data was collected using a questionnaire distributed to 300 customers from several Islamic banks in Lampung. The results showed that there was no statistically significant difference between the lifestyle patterns of users and non-users of the mobile banking application. However, the user's lifestyle has several common themes. Fashion, leadership, family awareness, health awareness, neglect, public awareness, and usability all have a significant impact on mobile app users, but cost awareness is where users use mobile banking apps. It does not have a significant impact on the methodology.